Dirasah netnografiyah haula ta’lim al-lughah al-‘arabiyah ‘abr wasaa’il al-tawasul al-ijtima’ii "YouTube" - Shobirin, Shobirin; Holimi, Muhammad; Ishlahuddin, Ishlahuddin; Shomad, Abdus (Lugawiyyat, 2025)
This netnographic study explores the landscape of Arabic language education within the virtual community of YouTube. Employing connectivism as its theoretical framework, the research investigates the structure of this online learning society and the mechanisms through which knowledge and education are exchanged. Data were collected through virtual observation and digital content analysis of Arabic language learning videos and their associated comments. The findings reveal a dynamic, interconnected network comprising content creators and learners engaging in both vertical and horizontal interactions. The study highlights the role of diverse instructional approaches, peer-to-peer support, and the influence of platform algorithms in shaping learning pathways. Ultimately, the research provides insights into the application of connectivist principles in the context of online Arabic language education, offering a deeper understanding of knowledge construction and exchange in digital learning environments.